Explaining company-level influences on individual career choices: Evidence from Belgium - Nele Soens; Ans De Vos; Dirk Buyens (Management Revue, 2006)
In the current career reality people not only make traditional career transitions such as entry into and exit from the labor market or upward in-company mobility, but also horizontal movements and transitions between employment and different social spheres such as household, care and leisure time. This broad perspective on career mobility that takes into account both traditional and new kinds of career steps is an important yet understudied area. Regarding the influences of making or not making a career transition, research has limited itself to individuals shaping their own career (i.e. micro level). Little research has examined the influence that organizations may exercise on the individual's career decision making process by means of their policies and practices (i.e. meso level). Drawing on Schmid's model of a transitional labor market (1998), this qualitative empirical research explores the factors at company level that individuals point to as obstructing or facilitating their career transitions. Results show that organizational policies and practices do play an important role in the individual's career trajectory as to whether or not he or she decides to undertake a transition. Implications for practitioners and policy makers are discussed.
Keywords: 650; career; transitions; labor market; Belgium; Erwerbsverlauf; Arbeitsmarkt; Belgien